Use of solar energy to dry paprika (capsicum annuum) - Alexandra Sánchez Zegarra (2019)
This technical scientific trial tries to give a design option to dry peppers in Arequipa región by building an experimental mixed solar dryer with energy accumulation (geomembranes) . we wil determine the adequete parameters for this process such as: temperatura, speed, drying time determinat variables will allow to control and optimize solar drying process. Products will be obtained with shorter times of solar drying , better quality and which may be the basis to develop higher capacity dryers.